2011
DOI: 10.1163/092050609x12578498935594
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adhesion and Fibrinogen Accretion on a Family of Elastin-Like Polypeptides

Abstract: Previous work in our laboratory showed the potential of using a human recombinant elastin-like polypeptide (ELP) as a thromboresistant coating. In this work we investigate the use of three particular ELPs (ELP1, ELP2 and ELP4), that differ by molecular weight and number of repeating hydrophobic and cross-linking domains, as coatings to improve blood-contacting properties. All three ELPs were passively adsorbed on Mylar surfaces. Differences in water contact angle and surface concentration were found among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(58 citation statements)
references
References 51 publications
5
52
1
Order By: Relevance
“…In a follow-up study, Woodhouse and colleagues reported platelet adhesion and fibrinogen adsorption on Mylar™ coated with three different ELPs. The authors observed a reduction in fibrinogen adsorption in all ELP-coated films; however, only the longer polypeptide chains exhibited decreased platelet adhesion (Srokowski et al, 2011). In a related study, an elastin-mimetic triblock protein polymer was evaluated by Chaikof and colleagues as a non-thrombogenic coating of impregnated ePTFE vascular grafts.…”
Section: Vascular Prostheses Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up study, Woodhouse and colleagues reported platelet adhesion and fibrinogen adsorption on Mylar™ coated with three different ELPs. The authors observed a reduction in fibrinogen adsorption in all ELP-coated films; however, only the longer polypeptide chains exhibited decreased platelet adhesion (Srokowski et al, 2011). In a related study, an elastin-mimetic triblock protein polymer was evaluated by Chaikof and colleagues as a non-thrombogenic coating of impregnated ePTFE vascular grafts.…”
Section: Vascular Prostheses Passivationmentioning
confidence: 99%
“…Albumin induces less platelet adsorption than other plasma proteins such as fibrinogen, which binds to the platelet GP IIb/IIIa receptor via arginine-glycine-aspartic acid (RGD) sequences (Zaidi et al, 1996;Srokowski et al, 2011). Despite albumin's rapid adsorption to the surface of a synthetic material, more thermodynamically favored proteins replace albumin on the surface (Andrade and Hlady, 1987).…”
Section: Vascular Prostheses Passivationmentioning
confidence: 99%
“…The dynamic nature of the adsorbed layer may be an important factor that contributes to its biological response [76]. Additionally, a decrease in fibrinogen accretion and platelet adhesion was observed for ELR-coated compared to uncoated surfaces, with the longest ELR coatings exhibiting lower levels of fibrinogen adsorption and platelet adhesion and therefore being the best thromboresistant coatings [77].…”
Section: Biofunctionality Control Using Elrsmentioning
confidence: 99%
“…The preparation of reconstituted whole blood containing labeled platelets and labeled fibrinogen has been described previously [21][22][23]. Blood was collected from healthy volunteers (human ethics approval REB-04-046, McMaster University).…”
Section: Preparation Of Re-constituted Whole Bloodmentioning
confidence: 99%